2014
DOI: 10.1016/j.biomaterials.2014.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Purification of human adipose-derived stem cells from fat tissues using PLGA/silk screen hybrid membranes

Abstract: The purification of human adipose-derived stem cells (hADSCs) from human adipose tissue cells (stromal vascular fraction) was investigated using membrane filtration through poly(lactide-co-glycolic acid)/silk screen hybrid membranes. Membrane filtration methods are attractive in regenerative medicine because they reduce the time required to purify hADSCs (i.e., less than 30 min) compared with conventional culture methods, which require 5-12 days. hADSCs expressing the mesenchymal stem cell markers CD44, CD73, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 39 publications
2
34
0
Order By: Relevance
“…Consistent with these results, many previous studies have also illustrated these kinds of functions of ADMSCs [22, 23]. In addition, it has been shown that bone marrow mesenchymal stem cell (BMSC) transplantation could enhance the closing pressure and leak point pressure in a rat model of SUI [24].…”
Section: Discussionsupporting
confidence: 73%
“…Consistent with these results, many previous studies have also illustrated these kinds of functions of ADMSCs [22, 23]. In addition, it has been shown that bone marrow mesenchymal stem cell (BMSC) transplantation could enhance the closing pressure and leak point pressure in a rat model of SUI [24].…”
Section: Discussionsupporting
confidence: 73%
“…Human adipose tissue was collected from the fat pads of human patients from the omentum and near the intestines (45–85 years old, six people) after obtaining informed consent. The adipose tissue cell solution (SVF, stromal vascular fraction) was made using a previously reported method162336. The number of hADSCs in the adipose tissue cell solution was evaluated using flow cytometry with antibodies to CD90, CD73, CD40, and CD34 and appropriate isotype antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…There are several possible methods of isolating hADSCs from SVF solution other than the conventional cell culture method on TCPS dishes: (a) MACS (magnetic-activated cell sorting) method20, (b) FACS (fluorescence-activated cell sorting) method2122, membrane filtration method152324, and membrane migration method16. MACS and FACS use antibodies to purify specific target cells such as CD166, CD105, CD90, CD73, CD44, and CD29 expressing cells (CD166 + , CD105 + , CD90 + , CD73 + , CD44 + , and CD29 + cells).…”
mentioning
confidence: 99%
See 2 more Smart Citations